Model Pembelajaran Think Pair Share (TPS) dalam Pembelajaran Membaca Pemahaman Cerpen - Djeje Sopandi; Iis Ristiani (Institut Nalanda, 2024)
This study aims to explain the ability to read and the effectiveness of TPS cooperative learning models in learning to read short story comprehension. This type of research is quantitative research with experimental methods. Data collection techniques used were test, observation, questionnaire and interview techniques. The data source is students of class IX Sekolah Menengah Pertama Negeri 2 Kota Sukabumi. Data analysis techniques in this study were conducted with a normality and homogeneity test. The results of this study indicate that the short story comprehension reading skills of class IX students of Sekolah Menengah Pertama Negeri 2 Kota Sukabumi after using the TPS learning model are in Very Good qualifications (BS) with an average value of 82.68, while reading short story comprehension before using cooperative learning think pair share type Grade IX students of Sekolah Menengah Pertama Negeri 2 Kota Sukabumi are of Enough qualification (C) with an average grade of 54.14.